2005
DOI: 10.1088/0953-4075/38/13/002
|View full text |Cite
|
Sign up to set email alerts
|

Positron and electron scattering from tetrahydrofuran

Abstract: We report results of total cross-section measurements for positron and electron scattering from the chemically and biologically important molecule tetrahydrofuran. We believe this is the first time such data have been reported in the literature. The positron measurements were conducted over the energy range of 0.1–20.0 eV, with the cross section being found to be strongly peaked at the lower energies. The electron energy range was 2–21 eV, with this cross section's main feature being a broad shape resonance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
82
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 28 publications
23
82
2
Order By: Relevance
“…These include measurements of elastic DCSs for THF, [11][12][13][14] THFA, 15 and 3HTHF. 16,17 Total cross sections for electron and positron scattering from THF, [18][19][20] 3HTHF, 21 and THFA (Refs. 22 and 23) have also been measured.…”
Section: Introductionmentioning
confidence: 99%
“…These include measurements of elastic DCSs for THF, [11][12][13][14] THFA, 15 and 3HTHF. 16,17 Total cross sections for electron and positron scattering from THF, [18][19][20] 3HTHF, 21 and THFA (Refs. 22 and 23) have also been measured.…”
Section: Introductionmentioning
confidence: 99%
“…Condensedphase experiments on thymidine and a single-strand oligonucleotide have demonstrated that slow electrons do indeed break the C-O phosphate-sugar bonds as well as the C-N base-sugar bonds, [60][61][62] and C-O bond breaking was also found in gas-phase DA to a model phosphodiester. 63 A few electron-collision studies, experimental and theoretical, have looked at the individual backbone constituents, i.e., ribose or deoxyribose and a phosphate group, [64][65][66][67][68][69] and others have also been made of electron collisions with backbone analogs such as tetrahydrofuran, 29,65,[68][69][70][71][72][73][74][75][76][77][78][79] tetrahydrofurfuryl alcohol, 71,72,80,81 fructose, 79 and dibutyl phosphate. 63 However, the only electron collision measurements involving nucleosides that we are aware of are the study by Zheng et al of thymine desorption from condensed-phase deoxythymidine 60 mentioned earlier, and the gas-phase studies by Abdoul-Carime et al 82 and by Denifl et al 83 of DA to deoxythymidine and 5-bromouridine, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…5. TCSs (×10 −20 m 2 ) for positron scattering from the cyclic ethers, as studied previously [8][9][10][11] at the University of Trento and also as a part of this investigation. See legend on the figure for further details.…”
Section: Tetrahydropyranmentioning
confidence: 91%
“…Some of the important physico-chemical properties of the present cyclic ethers and also those from our previous investigations. [8][9][10][11] Note that (a) denotes the value pertaining to the first or global energy minimum conformer, while (b) denotes the value pertaining to the second or next highest energy conformer. drawn from the rare gases, 27,28 for example.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation